Pseudopeptides with aldehyde or vinylsulfone warheads: Synthesis and antiproteasomal activity - Jorda, Radek; Molitorová, Veronika; Pilařová, Eliška; Vojáčková, Veronika; Řezníčková, Eva; Svobodová, Klára; Pauk, Karel; Imramovský, Aleš; Kryštof, Vladimír (Bioorganic chemistry, 2021)
The comparative study of new proteasome inhibitors based on salicylic acid-modified pseudo-tripeptides terminated with aldehyde or vinylsulfone is presented. We described the synthesis of 11 pairs of pseudopeptides and their properties related to the proteasome inhibition were determined. The effects of integrated amino acids (combinations of leucine, phenylalanine, tryptophan, proline, cyclohexylalanine or norleucine residues) on the activity of the proteasome were investigated. Compounds preferentially inhibited the chymotrypsin β5-subunit of the proteasome in cell-based assays compared with the β1- and β2-subunits, with IC50 values in mid-nanomolar ranges being obtained for the most active members. Our comparative study demonstrated that aldehydes were able to inhibit the proteasome in cells more effectively than vinylsulfones. These results were corroborated by the accumulation of polyubiquitinated proteins in treated cells, GFP accumulation in a reporter cell line and the ability of new compounds to induce apoptotic cell death.
Keywords: nádorové buněčné linie; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Aldehydes; vinylové sloučeniny; Vinyl Compounds; Ubiquitin; Proteasome Endopeptidase Complex; Proteasome Inhibitors; Proteasome; sulfony; Cell Line, Tumor; proteasomový endopeptidasový komplex; Sulfones; Peptides; Salicylamide; vztahy mezi strukturou a aktivitou; inhibitory proteasomu; Humans; aldehydy; molekulární struktura; peptidy; Apoptosis; Inhibitor; Structure-Activity Relationship; lidé; Molecular Structure